Pengaruh Dialek dalam Pertuturan Bahasa Melayu Standard: Pencerakinan Bunyi Berasaskan Spektrogram (Jurnal Bahasa, 2010)
The objective of this article is to show the influence of dialects, in particular Kelantanese Malay dialect, on the standard Malay spoken by native speakers of Kelantanese. The study identifies the pattern of nasalisation in Kelantanese speech via spectrographic analysis. This analysis focuses on the final syllable of specific words produced by Kelantanese speakers when conversing in different contexts, i.e. when using standard Malay language and non-standard language (the Kelantanese Malay dialect). Spectrographic analysis here refers to the study of phonetic alteration of vowels and consonants in the final syllable (i.e. whether formant frequency of an [a] vowel in the final syllable will be maintained or changed to [E], and whether the acoustic cues of vowel and consonant in the final syllable will be maintained or fade away). Phonetically, the pattern of nasalisation in Kelantan dialect differs from that of standard Malay. We may therefore assume that the characteristics of final syllable vowels and consonants spoken by Kelantan Malay speakers will be different when speaking Malay and the Kelantanese Malay dialect. This study, however, proves otherwise, with standard Malay being strongly influenced by the Kelantanese dialect.Keywords: nasalisation, Kelantanese dialect, Standard Malay Language, spektrographic analysis